1972
DOI: 10.1111/j.1748-1716.1972.tb05336.x
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Noradrenaline Turnover and Urinary Catecholamine Excretion in Trained and Untrained Rats during Rest and Exercise

Abstract: Rats were trained by daily swimming (1—2 h) during 15 weeks. The training caused a significant increase in heart weight. Cardiac noradrenaline (NA) and adrenal catecholamine (CA) contents were significantly increased in trained animals. When exposed to acute prolonged exercise the endogenous levels of cardiac NA decreased in untrained, but not in trained, rats. Resting cardiac NA turnover, as measured by rate of disappearance of exogenous 3H‐NA, was slower in trained than in untrained rats (T1/2= 52 h and 20 h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
14
1

Year Published

1974
1974
1996
1996

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(19 citation statements)
references
References 13 publications
4
14
1
Order By: Relevance
“…However, in some dog species training leads to bra dycardia which is not accompanied by hypertrophy [75], so other factors must be involved. Increased catecholamine content was found in the hearts of rats trained by swim ming [81 ] and hypertrophy in endurance-trained rats could be attenuated by ppblocker mctoprolol [82]. However, there are, surprisingly, no differences in the density of preceptors and no other hormonal changes which could explain the development of exercise hypertrophy [76], Recently, it has again been suggested that augmentation of coronary blood flow contributes to improvement in heart performance [83], Therefore, the link between growth of myocytes and growth of vessels and the extent to which changes in coronary circulation can contribute to cardiac growth should be considered.…”
Section: H Eartmentioning
confidence: 98%
“…However, in some dog species training leads to bra dycardia which is not accompanied by hypertrophy [75], so other factors must be involved. Increased catecholamine content was found in the hearts of rats trained by swim ming [81 ] and hypertrophy in endurance-trained rats could be attenuated by ppblocker mctoprolol [82]. However, there are, surprisingly, no differences in the density of preceptors and no other hormonal changes which could explain the development of exercise hypertrophy [76], Recently, it has again been suggested that augmentation of coronary blood flow contributes to improvement in heart performance [83], Therefore, the link between growth of myocytes and growth of vessels and the extent to which changes in coronary circulation can contribute to cardiac growth should be considered.…”
Section: H Eartmentioning
confidence: 98%
“…The water of the pool was circulated and its temperature was maintained at 36 'C. Previous reports have demonstrated that rats do not show marked changes in rectal temperature (Ostman, Sjostrand & Swedin, 1972) and that they can swim for 60 h in water at 36 'C (Dawson & Horvath, 1970), indicating that the water temperature of 36 'C is suitable for rats to swim in. During the exercise, the rats' conditions were carefully watched, and when the rats showed symptoms of fatigue, the exercise was stopped.…”
Section: Methodsmentioning
confidence: 99%
“…Exercise was stopped immediately if any animal showed signs of fatigue. The water was maintained at a temperature of 360°C since rats maintain a relatively constant rectal temperature under these conditions (Ostman, Sjostrand & Swedin, 1972) and can swim for up to 60 h in water at this temperature (Dawson & Horvath, 1970). In order to make allowance for any psychological effect of immersion, a control group of animals was caused to swim for short periods (3 min each day for 5 days each week for 4 weeks) without the neck weight.…”
Section: Methodsmentioning
confidence: 99%